Reevaluating the Sensory Account of Visual Working Memory Storage. Issue 10 (October 2017) - Xu, Yaoda
Abstract : Recent human fMRI pattern-decoding studies have highlighted the involvement of sensory areas in visual working memory (VWM) tasks and argue for a sensory account of VWM storage. In this review, evidence is examined from human behavior, fMRI decoding, and transcranial magnetic stimulation (TMS) studies, as well as from monkey neurophysiology studies. Contrary to the prevalent view, the available evidence provides little support for the sensory account of VWM storage. Instead, when the ability to resist distraction and the existence of top-down feedback are taken into account, VWM-related activities in sensory areas seem to reflect feedback signals indicative of VWM storage elsewhere in the brain. Collectively, the evidence shows that prefrontal and parietal regions, rather than sensory areas, play more significant roles in VWM storage. Trends: Recent findings from human fMRI decoding studies have provided renewed support for the sensory account of VWM storage. This account argues that brain areas involved in sensory processing also play important roles in the temporary storage of information in VWM. However, a detailed examination of human behavior, fMRI decoding, TMS, and monkey neurophysiology results showed very little support for the sensory account of VWM storage. Instead, both structural and experimental evidence supports prefrontal and posterior parietal cortices as brain regions playing more significant roles in VWM storage.